The Impact of the Covid-19 Pandemic on the Speaking Performance in English of Extroverted and Introverted Students at the Akademi Komunitas Mapindo Accommodation Study Program - Asriyani, Retny; Lindawati, Ni Putu (Akademi Komunitas MAPINDO, 2023)
This research aims to analyse the ability of speaking performance English in Extrovert and Introvert students after participating in online learning. The personality of extrovert students is that they show the courage to speak in front of the class and give opinions or opinions. Meanwhile, introverted students are people who prefer to be silent and speak as needed, and prefer to have few friends. The purpose of this study is to analyse the impact of online learning in the Covid-19 era on the ability to speak English in extroverted and introverted students. The research method used is a qualitative method with descriptive research. There were 10 subjects in this study, the students were 5 extrovert students and 5 introvert students. The instruments used in this study were observation and interviews. This research technique uses triangulation which consists of; Questionnaires, interviews, and documentation. This research applies 6 steps to analyse data; grouping, preparing data, reading the result data, viewing the result data, giving a code or mark, making a research description. The results show that the impact of the covid-19 pandemic online learning on students' speaking performance in English in the Akademi Komunitas MAPINDO accommodation study program differs between extrovert and introvert students. Changes in the learning system from online learning to offline learning show positive and negative impacts on students' speaking performance in English. The results of this study indicate that introvert students feel a more positive impact from online learning on their English speaking ability in English, on the other hand, extrovert students do not feel any positive impact from online learning on English. There is an increase in the speaking ability in English of introverted students when participating in online learning. Keywords: Personality, Extroversion, Introversion, Covid-19, Speaking Performance